Problematyka tożsamości personalnej w kontekście powołania i zatrudnienia jednoosobowego zarządu w jednoosobowej spółce z ograniczoną odpowiedzialnością - Dela, Mirosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Private companies limited by shares or by guarantee, managed by one person who is their sole shareholder, are seen as an alternative to business activities conducted on the basis of the Act on Freedom of Business Activity, thereby releasing the owner from personal liability for obligations of such entity. The specificity of these untypical companies is the creation of personal identity between the shareholder and the chairman of the board, leading to the necessity to perform legal actions “with oneself.” It has particular implications in the field of establishing an employment relationship with the chairman of the board in his own company. Imprecise provisions of the acts related to company law and labour law cause a lot of controversy in this matter. The author brings up the subject of appointing the sole shareholder, constituting the one-person board of directors, and the way of employing him in the company. He indicates a lack of possibilities to establish the employment relationship caused by the lack of essential elements of subordination, and suggests that the member of the board should be employed on the basis of a civil law agreement management contract.
Keywords: spółka z ograniczoną odpowiedzialnością lub poręczeniem; jednoosobowy zarząd; powołanie jedynego wspólnika do jednoosobowego zarządu; zatrudnienie członka jednoosobowego zarządu; umowa menedżerska